Effects of soybean fields on the health of Apis mellifera (Hymenoptera: Apidae) in the Chaco ecoregion - Monmany-Garzia, Ana Carolina; Chacoff, Natacha Paola; Aragón, Roxana; Sosa, Alexis Lionel; Aparicio, Virginia Carolina; Ayup, María Marta; Galindo Cardona, Alberto (Oxford University Press, 2025)
Honey bees (Apis mellifera) are important pollinators for natural and cultivated species. Due to their high sensitivity to stressors, they are also valuable indicators of environmental changes and agricultural management practices. In this study, we compared the performance and incidence of pesticides over sentinel hives within forest remnants with those within linear forest fragments (LFF) surrounded by soybean fields under conventional management. Sentinel hives in LFF showed some signs of deterioration, such as colony collapse, low numbers of brood frames, and pesticide occurrences, but honey production and the number of adult bees were similar to hives in the forest. Soybean pollen was scarce in honey and absent in bee bread, suggesting that bees may be relying more on wild plant species. We detected 5 pesticides (azoxystrobin, carbendazim, chlorpyrifos, imidacloprid, and coumaphos) in hives both at forests and LFF in pollen, bee bodies, and wax; pesticides in honey were detected in old sentinel hives (2 yr of exposition to agricultural conventional management). Only 2 of the 5 pesticides were applied in one of the farms under study, highlighting the importance of considering landscape-scale agricultural management. Our results indicate that conventional agriculture of soybean/maize primarily affected the performance of beehives, and pesticides were detected in honey only after long exposure to hives. Beekeeping in soybean fields in the Chaco could be feasible if cautions were followed, such as the conservation of forest fragments and key plant species, appropriate pesticide schedules, coordinated applications among farms, and linear forest remnants improvements.